New neoliberalism and the other : biopower, anthropophagy, and living money - Cocco, Giuseppe (Lexington Books, 2018)
This book proposes a shift in the very concept of neoliberalism as an ambivalent product of subjectivity. It is not resolved in dichotomies between the included and excluded, interior and exterior, capitalist and noncapitalist. Neoliberalism operates in blurred lines, through flexible structures, and amid internal gradients and varying tensions.